MORPHOMETRIC CHARACTERISTICS OF THE RENAL PYRAMIDS OF THE HUMAN KIDNEY INFERIOR EXTREMITY, CONSISTING OF TWO EXCRETORY SECTORS - Shuba, D.G. (World of Medicine and Biology, 2015)
The aim was to study the features of individual anatomical variability on renal pyramids sections of the kidney inferior extremity at mature people and the elderly. As a research material were used obtained with a macrotom topographical sections of 89 human kidney inferior extremities, distributed by age groups, in each of which we have studied a number of renal pyramids, their topography and morphometric characteristics. The largest average base diameter of renal pyramids in the kidney inferior extremity including two excretory sectors defined in the lower posterolateral pyramid (PRipl) is14,75 mm and the smallest in the lower posteromedial pyramid (PRips) is 8,84 mm. The minimum diameter of the smallest foundation was identified in the lower the posterior-median pyramid (PRips), is 3,4 mm and the highest minimum diameter of 6.2 mm wss defined in the lower posterolateral (PRipl) pyramid. The height of the inferior extremity pyramids all of the kidneys have two excretory sector. The lowest average height was in the lower anteromedian pyramid (PRias) on the front surface, and at the lower posterior median pyramid (PRips) on the rear surface of the organ it is 9.94 mm and 8.94 mm accordingly. The largest average height is revealed in the lower lateral pyramids on both (front and back) surfaces of inferior extremity of the kidneys and is 14.37 mm and 14.75 mm accordingly. The smallest absolute value of the height belongs to two pyramids: the lower renal pyramid (PRi) and the lower posterolateral pyramid (PR ipl) 4 mm, and the highest minimum belongs to the lower anterolateral pyramid (PRial) 7 mm. The maximum height indexes of the inferior extremity pyramids of the kidney are reasonably expressed. The height of the lower anteromedian renal pyramids (PRias) is 18 mm and the height of the lower anteromedial pyramid (PRiam) is 29 mm. The pyramid inferior extremity volume of the two sector kidney also varies quite clearly. The average volume of the lower posterior median pyramid (PRips) is 392.21 mm ³, while the average volume of the lower anterolateral pyramid (PRial) exceeds it about three times and is 1777.58 mm ³. In the two-sector kidney the lowest average volumes of the pyramids both on the front and on the rear surfaces belong to the lower anteromedian renal pyramid (PRias) and to the lower posterior-median pyramid (PRips), and the highest average volumes of the pyramids in the kidney inferior extremity at the lower posterolateral pyramid (PRipl) and the lower anterolateral pyramid (PRial) on both surfaces of the organ. This suggests a redistribution of the renal parenchyma in the development process to the lateral surfaces of the organ on both surfaces thereof. The lower anteromedian renal pyramid (PRias) has the smallest gap between minimum and maximum volume figures (106.2 mm ³ and 1646 mm ³, accordingly). The difference between the minimum and the maximum figures of the other inferior extremity pyramids is much more expressed. The minimum volume of the lower anteromedial pyramid (PRiam) is 44.4 mm ³, and the maximum is 5775.0 mm ³. The smallest minimum volume identified in the lower posterior median pyramid (PRips) is 27,0 mm ³, to it also belongs the smallest maximum amount of 1436.7 mm ³, that in spite of small volume indexes of the pyramid shows its stable presence in the two sector kidney inferior extremity. The total pyramids volume of the front surface of the kidney inferior extremity which excretory tree contains two excretory sectors is more than the total volume of the pyramids located on the rear surface of the inferior extremity of such organ. The largest by volume are lateral pyramids on both surfaces, the volume of the anterolateral pyramid (PRial) is more than the volume of the posterolateral pyramid (PRipl).